Impact of Employee Training and Development on Organizational Productivity in IT Industry of Chennai city - K. M, Ramya Krishna (The journal of contemporary issues in business and government, 2022)
This research article aims “To measure the impact of training and development attributes on organizational productivity.” The paper applies data reduction using Reliability Test, Exploratory Factor Analysis and Multiple Linear Regression on a sample of 328 respondents drawn from 5 IT companies in the Chennai and condenses a set of 12 training and development statements converted into a two factors. The present study proposes a model of the impact of employee training and development on organizational productivity of IT companies. The present study proposes a model of the impact of employee training and development on organizational productivity of the IT companies. The study found that training and developments are impacting significantly the organizational productivity of the IT companies. Therefore, IT people should focus on the above factors to provide enrich employee training and development. The study investigated the impact of employee training and development on organizational productivity of the IT companies, concluded that employee training and developments are impacting significantly the organizational productivity of the IT companies.